2021
DOI: 10.1016/j.ijid.2020.09.1459
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B surface antigen and serological markers of other endemic infections in HIV-infected children, adolescents and pregnant women in Sierra Leone: A cross-sectional study

Abstract: To assess the prevalence of serological markers of HBV and endemic acute and chronic infections (HAV, HCV, CMV, HTLV-1/2 and syphilis) in HIV-infected children, adolescents and pregnant women in Sierra Leone. Method: We conducted a cross-sectional study at the national children's and women's hospitals in Freetown. Logistic regression was used to assess predictors of HBsAg positivity. Results: 183 HIV-infected participants were enrolled, comprising children (n = 88), adolescents (n = 47) and pregnant women (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
1
19
1
1
Order By: Relevance
“…Current international ART treatment guidelines recommend a dual NRTI-backbone in combination with an INSTI or a boosted-PI with a high genetic barrier to developing resistance such as darunavir/ritonavir (DRV/r) in the treatment of HIV-infected individuals [ 12 , 19 , 20 , 21 ]. Sierra Leone is an INSTI-naïve stetting, as INSTI-based ART was only recently introduced in 2021.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current international ART treatment guidelines recommend a dual NRTI-backbone in combination with an INSTI or a boosted-PI with a high genetic barrier to developing resistance such as darunavir/ritonavir (DRV/r) in the treatment of HIV-infected individuals [ 12 , 19 , 20 , 21 ]. Sierra Leone is an INSTI-naïve stetting, as INSTI-based ART was only recently introduced in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, patients failing first-line ART based on the 2017 ART guidelines in Sierra Leone have limited options for second-line therapy, as estimated by the GSS ( Table 2 ). Secondly, with high rates of HIV/HBV coinfection in this setting (up to 22% based on previous studies by our group) [ 11 , 12 ]—a large proportion of patients on 3TC-based and/or TDF-sparing ART regimens are likely to be receiving suboptimal treatment for both HIV and HBV infections, heightening their risk for progression to AIDS, liver cirrhosis, and end-stage liver disease. Thus, screening for HBV in all HIV-infected patients before ART initiation and at the time of switching ART is essential to guiding optimal ART choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are currently no nationally representative studies, Sierra Leone is regarded as a hyperendemic country, with an estimated countrywide HBV seroprevalence rate of 8% to 10% [8,9]. Pregnant women appear to be disproportionately impacted by the HBV epidemic, yet few studies have described the epidemiology of HBV in this vulnerable group in Sierra Leone [10]. A handful of small studies conducted among pregnant women in Sierra Leone have reported HBsAg seroprevalence rates ranging from 6% to 18.8% [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Os meios de propagação do vírus, comumente, ocorrem por aleitamento materno, por transmissão vertical, sexual e parenteral (Ramos-Rincón et al, 2021;Yendewa et al, 2021). Na epidemiologia, determinam precauções para o controle e prevenção aos cônjuges, pais, filhos, ou seja, aos que mantêm maior contacto com um soroprevalênte (Aquilo, Ramos, 2019).…”
Section: Introductionunclassified